2018
DOI: 10.4236/psych.2018.97108
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate Synchrony in Psychological Counseling: A Case Study

Abstract: The present study examined interpersonal synchrony during psychological counseling, focusing on heart rate synchrony. In psychological counseling and psychotherapy, embodied synchrony is considered an important factor related to building rapport and empathy. Recent interpersonal synchrony/coordination studies have addressed this issue, not only at the behavioral level but also at the neurological (brain activity) and physiological (cardiac activity) levels. However, there is little known literature on heart ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 36 publications
2
17
0
Order By: Relevance
“…Di Mascio et al (1955) were likely the first to study the interpersonal correlation of HR, exploring three single cases of psychoanalytic interviews. Kodama et al (2018) reported a single-case study where HR synchrony correlated with qualitative measures. Interpersonal HRV was again first explored by the Di Mascio group (Di Mascio et al, 1957), who reported in-phase HRV synchrony in observer-coded tension segments and anti-phase synchrony in antagonistic segments.…”
Section: Research On Physiological Synchrony In Psychotherapy and Psymentioning
confidence: 99%
“…Di Mascio et al (1955) were likely the first to study the interpersonal correlation of HR, exploring three single cases of psychoanalytic interviews. Kodama et al (2018) reported a single-case study where HR synchrony correlated with qualitative measures. Interpersonal HRV was again first explored by the Di Mascio group (Di Mascio et al, 1957), who reported in-phase HRV synchrony in observer-coded tension segments and anti-phase synchrony in antagonistic segments.…”
Section: Research On Physiological Synchrony In Psychotherapy and Psymentioning
confidence: 99%
“…Improvisational performance is more like everyday social interaction, in the sense that it also has complex aspects emerging from real-time interaction (Walton et al, 2018). The dynamical methods (e.g., recurrence analysis) are also expected to reveal the creative process in detail using more advanced techniques (e.g., the windowed sliding method; Coco and Dale, 2014;Kodama et al, 2018). We also aim to apply the framework not only to experimental situations but also to more ecological situations, such as the practical field of artistic performance, natural daily interaction (D'Ausilio et al, 2015;Dale, 2015;Sekine and Kita, 2015;Shimizu and Okada, 2018) and clinical interaction in psychological and medical fields (Zivotofsky and Hausdorff, 2007;Nagaoka and Komori, 2008;Ramseyer and Tschacher, 2011;Goldstein et al, 2020) involving speech-motion coordination in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Another group of recent studies examining autonomic arousal in psychotherapy focus on physiological concordance or linkage, 'the social coupling of two (or more) individuals in the hereand-now of a communication context that emerges alongside, and in addition to, their verbal exchanges' (Tschacher and Meier, 2020, p. 558). Some early studies showed evidence for autonomic concordance between clients and therapists (e.g., DiMascio et al, 1957), a finding that has been explored further more recently (e.g., Marci et al, 2007;Villmann et al, 2008;Karvonen et al, 2015;Seikkula et al, 2015Seikkula et al, , 2018Kodama et al, 2018;Tschacher and Meier, 2020). Findings from these studies are mixed; however, one finding that has been shown across several studies on psychotherapy sessions (as well as in studies of simulated sessions, e.g., Marci and Orr, 2006;Messina et al, 2013;Palmieri et al, 2018) is a correlation between ratings of empathy and the degree of physiological linkage between therapist and client.…”
Section: Interpersonal Physiology and Psychotherapy Processmentioning
confidence: 99%